The combined effects of Cd and Pb enhanced metal binding by root cell walls of the phytostabilizer Athyrium wardii (Hook.). (March 2020) - Zhan, Juan; Huang, Huagang; Yu, Haiying; Zhang, Xizhou; Zheng, Zicheng; Wang, Yongdong; Liu, Tao; Li, Tingxuan
Abstract: Cell wall acts as a major metal sink in plant roots, while a few studies focused on root cell wall binding in plants for the phytostabilization of multi-metal contaminated soils. A pot experiment was performed to characterize root cell wall properties of the mining ecotype (ME) and non-mining ecotype (NME) of Athyrium wardii (Hook.) in response to Cd and Pb. The cell wall was found to be the major sink for Cd (41.3–54.3%) and Pb (71.4–73.8%) accumulation in roots of the ME when exposed to Cd and/or Pb. The ME showed more Cd and Pb accumulation in root cell walls when exposed to Cd and Pb simultaneously, compared with those exposed to single Cd or Pb as well as the NME, suggesting some modifications for cell walls. The uronic acid contents of pectin and hemicellulose 1 (HC1) in root cell walls of the ME increased significantly when exposed to Cd and Pb simultaneously, suggesting enhanced cell wall binding capacity, thus resulting in more Cd and Pb bound to pectin and HC1. In particular, pectin was found to be the predominant binding site for Cd and Pb. Greater pectin methylesterase activity along with a lower degree of methylesterification were observed in the cell walls of the ME when exposed to Cd and Pb simultaneously. Furthermore, the ME present more O–H, N–H, C–OH, C–O–C, C–C and/or Ar–H in root cell walls when exposed to Cd and Pb simultaneously. These changes of root cell wall properties of the ME lead to enhanced cell wall binding ability in response to the co-contamination of Cd and Pb, thus could be considered a key process for enhanced Cd and Pb accumulation in roots of the ME when exposed to Cd and Pb simultaneously. Graphical abstract: Image 1 Highlights: Cell wall was the major sink for Cd and Pb accumulation in roots of ME. The exposure of Cd and Pb induced more pectin and HC1 accumulation in roots of ME. ME showed more low-methylesterified pectin accumulation in root cell walls. ME showed more O–H, N–H, C–OH, C–O–C, C–C and/or Ar–H in root cell walls. More Cd and Pb were bound to root cell walls of ME when exposed to Cd and Pb. Abstract : The enhanced cell wall binding ability involved in Cd and Pb accumulation in roots of the ME exposed to Cd and Pb show great benefit to the phytostabilization of Cd and Pb co-contaminated soils.